2022
DOI: 10.1111/mpp.13203
|View full text |Cite
|
Sign up to set email alerts
|

The novel avirulence effector AlAvr1 from Ascochyta lentis mediates host cultivar specificity of ascochyta blight in lentil

Abstract: Ascochyta lentis is a fungal pathogen that causes ascochyta blight in the important grain legume species lentil, but little is known about the molecular mechanism of disease or host specificity. We employed a map‐based cloning approach using a biparental A. lentis population to clone the gene AlAvr1‐1 that encodes avirulence towards the lentil cultivar PBA Hurricane XT. The mapping population was produced by mating A. lentis isolate P94‐24, which is pathogenic on the cultivar Nipper and avirulent towards Hurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It has been reported that the nuclear effector ArPEC25 of A. rabiei manipulated the lignin biosynthesis of chickpea for invasion by targeting the transcription factor CaβLIM1a ( 37 ). The effector AlAvr1 from A. lentis mediated the host cultivar specificity of ascochyta blight of lentil ( 38 ). Homolog analysis found that the ArPEC25 homologs were highly conserved, with over 80% amino acid identities in all available genomes of Ascochyta spp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the nuclear effector ArPEC25 of A. rabiei manipulated the lignin biosynthesis of chickpea for invasion by targeting the transcription factor CaβLIM1a ( 37 ). The effector AlAvr1 from A. lentis mediated the host cultivar specificity of ascochyta blight of lentil ( 38 ). Homolog analysis found that the ArPEC25 homologs were highly conserved, with over 80% amino acid identities in all available genomes of Ascochyta spp.…”
Section: Discussionmentioning
confidence: 99%